2022
DOI: 10.1007/s40692-022-00240-0
|View full text |Cite
|
Sign up to set email alerts
|

A review of using digital game-based learning for preschoolers

Abstract: In recent years, the use of digital game-based learning (DGBL) in the early childhood learning process has been growing. Recent research shows that DGBL has the potential to create new forms of childhood learning, it is not yet clear how applications can affect young students' learning. There are also not sufficient studies to analyze the significant features of DGBL in this area in early childhood. Therefore, to better understand the impact on childhood DGBL education, this article reviews the systematic lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 61 publications
0
7
0
2
Order By: Relevance
“…In addition to these, Garcia and Mangaba (2017) stipulated in their study that GBL is often used for curricular knowledge. In addition to these, several studies have also pointed out that GBL, together with technology, can further support student learning in various areas (e.g., Behnamnia et al, 2022;Beşaltı & Kul, 2021;Bringula et al, 2018;Garcia, 2020;Godoy Jr., 2020). Other studies have also indicated that GBL with technology creates a positive effect on students as well as on achieving learning outcomes (Cahyana et al, 2017;Chao et al, 2018).…”
Section: Game-based Learning For Mathematicsmentioning
confidence: 98%
“…In addition to these, Garcia and Mangaba (2017) stipulated in their study that GBL is often used for curricular knowledge. In addition to these, several studies have also pointed out that GBL, together with technology, can further support student learning in various areas (e.g., Behnamnia et al, 2022;Beşaltı & Kul, 2021;Bringula et al, 2018;Garcia, 2020;Godoy Jr., 2020). Other studies have also indicated that GBL with technology creates a positive effect on students as well as on achieving learning outcomes (Cahyana et al, 2017;Chao et al, 2018).…”
Section: Game-based Learning For Mathematicsmentioning
confidence: 98%
“…Las redes neuronales Artificiales (ANN) son una sucesión de capas que contienen un gran número de unidades interconectadas entre las llamadas neuronas [13]. Localidad espacial de los datos de entrada (SLID) es un método que permite la reducción de las operaciones de memoria y computación para lograr realizar un modelo más eficiente [14]. De la misma forma, Machine Learning (ML) es una rama de la inteligencia artificial que puede ser usada en múltiples tareas con el fin de predecir alguna información futura [15].…”
Section: Resultados Y Discusionesunclassified
“…Similarly, a study by Craig et al (2016) found that a game-based program improved cooperation and reduced aggression in preschool children. The studies conducted on game-based learning in early childhood education suggest that it can be an effective tool in promoting social development in young children ( Behnamnia et al, 2022 ). Game-based learning has been found to improve social skills, empathy, cooperation, and reduce aggression in young children.…”
Section: Discussionmentioning
confidence: 99%